2017
DOI: 10.1016/j.matcom.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and stability in retail competition

Abstract: Retail competition today can be described by three main features: i) oligopolistic competition, ii) multi-store settings, and iii) the presence of large economies of scale. In these markets, firms usually apply a centralized decisions making process in order to take full advantage of economies of scales, e.g. retail distribution centers. In this paper, we model and analyze the stability and chaos of retail competition considering all these issues. In particular, a dynamic multi-market Cournot-Nash equilibrium … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The synergy of both retail formats is easily achievable. In reality, there has been competition between the two formats and the development of oligopoly (Villena & Araneda, 2017). This problem has occurred in many emerging market countries (Bronnenberg & Ellickson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The synergy of both retail formats is easily achievable. In reality, there has been competition between the two formats and the development of oligopoly (Villena & Araneda, 2017). This problem has occurred in many emerging market countries (Bronnenberg & Ellickson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This part of the business world is at the forefront of these changes, dealing with strong competition and having to adapt to the quickly shifting preferences of customers. The dynamic nature of consumer behaviors and the intense competition in the retail sector make it a dynamic and challenging arena to navigate, [2].…”
Section: Introductionmentioning
confidence: 99%
“…ey demonstrated that the manufacturer's profit is higher with asymmetric channel power than with symmetric channel power. Villena and Araneda [21] explored the stability and chaos of a retail competition and concluded that retail multistore competition is less stable than traditional small business. Yuan and Hwarng [22] investigated the demand dynamics, under a demandbased pricing policy, of a frequently purchased service with considerations of social interaction and customers' adaptively forward-looking behavior.…”
Section: Introductionmentioning
confidence: 99%